2004
DOI: 10.1097/00001888-200403000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Unprofessional Behavior in Medical School Is Associated with Subsequent Disciplinary Action by a State Medical Board

Abstract: Problematic behavior in medical school is associated with subsequent disciplinary action by a state medical board. Professionalism is an essential competency that must be demonstrated for a student to graduate from medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
298
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(315 citation statements)
references
References 11 publications
4
298
0
13
Order By: Relevance
“…Such propositions are in line with findings from recent government enquiries in the UK (Francis 2013;Cavendish 2013) which highlighted Selection methods in healthcare professions: where are we now… 237 major concerns about the level of compassionate care giving from healthcare professionals. Papadakis et al (2004) finding that unprofessional behaviour in medical school is associated with subsequent disciplinary action by a state medical board in the USA also resonates here, as it does with our earlier points about the importance of longitudinal studies and appropriate outcome measures (Papadakis et al 2004). More research is needed to examine the practical and political implications of this approach to screening candidates, and to consider alternatives to both this and the status quo.…”
Section: Greater Focus On Theoretical Developmentssupporting
confidence: 79%
“…Such propositions are in line with findings from recent government enquiries in the UK (Francis 2013;Cavendish 2013) which highlighted Selection methods in healthcare professions: where are we now… 237 major concerns about the level of compassionate care giving from healthcare professionals. Papadakis et al (2004) finding that unprofessional behaviour in medical school is associated with subsequent disciplinary action by a state medical board in the USA also resonates here, as it does with our earlier points about the importance of longitudinal studies and appropriate outcome measures (Papadakis et al 2004). More research is needed to examine the practical and political implications of this approach to screening candidates, and to consider alternatives to both this and the status quo.…”
Section: Greater Focus On Theoretical Developmentssupporting
confidence: 79%
“…Papadakis et al reported a case-control study of all graduates from a single medical school who were subsequently disciplined by a state medical board. 5 Ninety-five percent of the disciplinary actions were for deficiencies in professionalism; the prevalence of concerning comments in medical school files was 38% in the disciplined physicians and 19% in controls. Papadakis et al then identified the specific types of inappropriate behaviour in medical school that were most predictive of disciplinary action against practicing physicians with unprofessional behaviour.…”
Section: Predicting Problem Patterns Of Behaviour In Physiciansmentioning
confidence: 99%
“…In a review article, van Mook et al (2014) examines the multiple issues related to the identification and remediation of ''dyscompetent'' residents, particularly in the area of professionalism. And an original study by Santen et al (2014) extends the findings of two landmark studies by Papadakis et al (2004Papadakis et al ( , 2008, which showed that unprofessional behavior in practice was apparently predictable from performance in medical school. Both studies used a ''case control'' design in which individuals who had the outcome of interest (discipline by a state licensing body)-''cases'' were compared to a random sample of doctors who were not reported-''controls''.…”
mentioning
confidence: 74%